2020
DOI: 10.1155/2020/1348914
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Degranulation and Adenosine Release:Acupoint Specificity for Effect of Electroacupuncture on Pituitrin‐Induced Acute Heart Bradycardia in Rabbits

Abstract: Acupuncture is a medical modality based on the theory of traditional Chinese medicine, and its effect is relatively dependent on acupoint specificity. However, there is little knowledge on acupoint specificity versus acupuncture outcomes because of the deficiency of rigorous investigation on this topic, which has impeded the growing legitimacy of acupuncture in the mainstream of medicine as an evidence-based therapy. Therefore, it is of utmost importance to clarify this critical issue. The present study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Moreover, He et al found that the concentration of substance P, a calcitonin gene related peptide, at the same acupoint, is different under normal, pathological, and acupuncture conditions [ 51 ]. Using high-performance liquid chromatography (HPLC) to measure the adenosine concentration at acupoints, Wang et al found significant differences before and after modeling and acupuncture [ 52 ]. These findings imply a dynamic variation of chemicals at the acupoints, manipulated by the inner environment or the external stimulation.…”
Section: Characteristics Of Mast Cells and Its Functionmentioning
confidence: 99%
“…Moreover, He et al found that the concentration of substance P, a calcitonin gene related peptide, at the same acupoint, is different under normal, pathological, and acupuncture conditions [ 51 ]. Using high-performance liquid chromatography (HPLC) to measure the adenosine concentration at acupoints, Wang et al found significant differences before and after modeling and acupuncture [ 52 ]. These findings imply a dynamic variation of chemicals at the acupoints, manipulated by the inner environment or the external stimulation.…”
Section: Characteristics Of Mast Cells and Its Functionmentioning
confidence: 99%
“…26,27 Therefore, in related studies, non-acupoints were usually used as sham control to verify the specificity of acupoints. 28,29 The non-acupoint area parallel to the acupoint and meridians were usually selected as the contrast sites. Stimulating the non-acupoint sites generates definite effects, but not limited to the local nearby effects.…”
Section: Discussionmentioning
confidence: 99%
“…After the stimulation at acupoint, the Qi effect, degranulation of mast cells, adenosine release, and the regulation of brain network and target organ are also different. 27,29,30 Therefore, whether strong appetite or moderate appetite, the same acupoint stimulation plays the similar effect. This trial has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…There are three main ways of MC activation: immunogenic, neurogenic and physical activation [ 4 , 29 ]. Many studies have confirmed that MCs play a central role in the initiation mechanism of acupuncture analgesic via degranulation [ 17 , 30 , 31 , 32 , 33 ]. In acute adjuvant arthritis (AA) model rats, acupuncture can induce the degranulation of subcutaneous MCs in treated ST36 [ 30 , 32 ], which can be prevented by local pre-administration of cromolyn (CRO), a stabilizer of MCs ( Figure 5 ).…”
Section: Activation Of Mcs Contributes To Acupuncture Analgesiamentioning
confidence: 99%
“…Besides manual acupuncture, electroacupuncture also can mediate Ado aggregation. In pituitrin-induced acute heart bradycardia rabbits, Ado accumulation occurs in Neiguan point (PC6) treated by 30-min electroacupuncture [ 33 ]. In ankle inflammatory or neuropathic pain model mice, activation of Ado A1 receptors in acupoint ST36 by 2-Chloro- N 6-cyclopentyladenosine (CCPA), a specific agonist of A1 receptors, has an anti-nociceptive effect [ 69 ].…”
Section: Mediators Of Acupuncture Signalingmentioning
confidence: 99%